Pengaruh Layanan Bimbingan Pribadi-Sosial terhadap Kepercayaan Diri (Self Confident) Siswa di SMA Negeri 1 Wanasaba Lombok Timur - FIRAD WIJAYA FIRAD (Al-INSAN Jurnal Bimbingan Konseling dan Dakwah Islam, 2022)
Given the personal life experience of students everyday can not be separated from the social interactions that exist in the school environment and society, but where the student is a social being whose ability level can be said to be very limited, and in dire need of help in the form of guidance. conducive environment, therefore education appears in the context of the formation of human character that will make good changes in individuals who are more qualified than before. Because of the quality of self-confidence possessed by individuals in forming a complete personal character, meaning that life is in accordance with what should be in the formation of social, intellectual, moral, spiritual character and so on. The purpose of this study was to determine whether there is an effect of Personal-Social Guidance services on the self-confidence of students at SMA Negeri 1 Wanasaba, East Lombok. The type of research used in this research is quantitative research. The research subjects are 466 students in the school. The data collection method used is a self-confident and personal-social guidance questionnaire scale. The results of this study indicate that the role of personal-social guidance services is very influential on the self-confidence of students at SMA Negeri 1 Wanasaba. It is known that the rxy value is 0.301, then this value is consulted with the r value of the product moment table at a significance level of 5% with N = 82, it turns out that the limit of the null hypothesis acceptance rate (Ho) shown in the table of r product moment values ​​is 0.279. This fact indicates that the r value of the data analysis results is above the limit of the null hypothesis acceptance rate (Ho) or the calculated r value of 0.301 is greater than the r value of the product moment table of 0.279 (0.301 > 0.279). This means that the results of data analysis in this study are "Significant".